Penyelesaian Sengketa dalam Perjanjian Joint Venture - Elwinnor, Ario; Dewanto, Putra Rezki; Riyandono, Aji Yudo; Yonata, Yohan (Universitas Sains dan Teknologi Komputer, 2025)
Joint ventures have experienced significant growth as a means to enhance cooperation between two or more companies from different countries in establishing a joint business entity. Joint ventures are regulated under Law Number 25 of 2007 concerning Investment. One notable case of joint venture in Indonesia involves a breach of contract between PT Layar Santosa Shipping and Wallem & Co., where Wallem & Co. failed to fulfill the obligations agreed upon in the joint venture agreement. This study employs a normative juridical method, with data collected through a literature review based on secondary data sources. The aim of this research is to examine the dispute resolution mechanism in joint venture agreements that include an arbitration clause.